Individual-level factors influencing voter turnout in the 2014 European Parliament election - Shapovalov, S. (Социология: теория, методы, маркетинг, 2019)
The participation of EU citizens in the European Parliament elections is much lower than in the national elections and differs significantly across the EU member states. The articled is aimed at finding out the factors that influence the participation of EU citizens in the elections to the European Parliament. The study outlines the theoretical approaches to understanding the phenomenon of the European Parliament elections and the assumptions of researchers about the factors that may influence the electoral activity of citizens. According to second-order elections theory by Karlheinz Reif and Hermann Schmitt citizens perceive European Parliament elections as less im portant than national elections that results in lower participation. However, the behavior of voters may also be affected by a number of factors which may be regarded as individual-level motivations (trust in national and European authorities, attitudes towards EU institutions etc.). With use of binary logistic regression method it was defined which factors influenced the participation of citizens in the European Parliament election 2014 and explained the differences in the electoral activity of citizens of different EU countries. The nature of the identified factors that influence the participation of citizens in the elections to the European Parliament suggests that the second-order elections theory is still valid.